Implementation of a flywheel energy storage system for space applications - Celikel, Resat; Ozdemir, Mehmet; Aydogmus, Omur (Tubitak Scientific & Technological Research Council Turkey, 2017)
A satellite power system requires solar panels to provide energy and orientation. There are two regions in the orbital path of the satellite: the dark and bright region. The energy is provided by solar panels in the bright region and by flywheel energy storage system (FESS) in the dark region. Brushless DC (BLDC) motors are widely used in the FESS due to their low weight, high power density, high efficiency, high reliability, and high speed. Some mechanical resonances may occur due to physical features of the mechanical parts. Therefore, the current of the BLDC is dramatically increased because of the mechanical resonance. In this work, a current reference method was used to protect the power systems of the satellite from the current spikes of the solar power system. The parameters of the PI controller were calculated by using genetic algorithms. A FESS was designed and experimentally performed for high speed operation at about 20 krpm in the vacuumed environment.
Keywords: Brushless motors; current reference method; energy storage; flywheel; genetic algorithms